Mining on the frontier: Archaeological excavation of the historical component at Canteen Kopje, Northern Cape Province, South Africa. (20th March 2022) - Chazan, Michael; Sumner, Alexandra; Horwitz, Liora Kolska; Morris, David
Abstract: Canteen Kopje was a prominent location within the spread of nineteenth century mining camps at Klipdrift along the Vaal River. This article presents the results of excavation of the historical component of Canteen Kopje that produced an artifact assemblage in which European manufactured ceramics and glass are associated with objects of local manufacture, which attests to the cultural interaction that took place in the context of early mining. These finds of material culture are associated with a faunal assemblage of wild animals primarily the remains of quagga, a species that was soon to go in extinct. Based on historical documentation and pictorial representation it is argued that the earliest Vaal River diamond diggings here represent a stage of extractive economies in southern Africa when the rigid control of space and people that emerged subsequently was not yet fully developed.